Characterizing the reflectivity of handheld display devices. Issue 8 (21st July 2014) - Liu, Peter; Badano, Aldo
Abstract : Purpose: With increased use of handheld and tablet display devices for viewing medical images, methods for consistently measuring reflectivity of the devices are needed. In this note, the authors report on the characterization of diffuse reflections for handheld display devices including mobile phones and tablets using methods recommended by the American Association of Physicists in Medicine Task Group 18 (TG18). Methods: The authors modified the diffuse reflectance coefficient measurement method outlined in the TG18 report. The authors measured seven handheld display devices (two phones and five tablets) and three workstation displays. The device was attached to a black panel with Velcro. To study the effect of the back surface on the diffuse reflectance coefficient, the authors created Styrofoam masks with different size square openings and placed it in front of the device. Overall, for each display device, measurements of illuminance and reflected luminance on the display screen were taken. The authors measured with no mask, with masks of varying size, and with display‐size masks, and calculated the corresponding diffuse reflectance coefficient. Results: For all handhelds, the diffuse reflectance coefficient measured with no back panel were lower than measurements performed with a mask. The authors found an overall increase in reflectivity as the size of the mask decreases. For workstations displays, diffuse reflectance coefficients were higher when no back panel was used, and higher than with masks. In all cases, as luminance increased, illuminance increased, but not at the same rate. Conclusions: Since the size of handheld displays is smaller than that of workstation devices, the TG18 method suffers from a dependency on illumination condition. The authors show that the diffuse reflection coefficients can vary depending on the nature of the back surface of the illuminating box. The variability in the diffuse coefficient can be as large as 20% depending on the size of the mask. For all measurements, both luminance and illuminance increased as the size of the display window decreased. The TG18 method does not account for this variability. The authors conclude that the method requires a definitive description of the back panel used in the light source setup. The methods described in the TG18 document may need to be improved to provide consistent comparisons of desktop monitors, phones, and tablets.